Complete intracranial response to talimogene laherparepvec (T-Vec), pembrolizumab and whole brain radiotherapy in a patient with melanoma brain metastases refractory to dual checkpoint-inhibition. Issue 1 (6th April 2018) - Blake, Zoë; Marks, Douglas K.; Gartrell, Robyn D.; Hart, Thomas; Horton, Patti; Cheng, Simon K.; Taback, Bret; Horst, Basil A.; Saenger, Yvonne M.
Abstract : Background: Immunotherapy, in particular checkpoint blockade, has changed the clinical landscape of metastatic melanoma. Nonetheless, the majority of patients will either be primary refractory or progress over follow up. Management of patients progressing on first-line immunotherapy remains challenging. Expanded treatment options with combination immunotherapy has demonstrated efficacy in patients previously unresponsive to single agent or alternative combination therapy. Case presentation: We describe the case of a patient with diffusely metastatic melanoma, including brain metastases, who, despite being treated with stereotactic radiosurgery and dual CTLA-4/PD-1 blockade (ipilimumab/nivolumab), developed systemic disease progression and innumerable brain metastases. This patient achieved a complete CNS response and partial systemic response with standard whole brain radiation therapy (WBRT) combined with Talimogene laherparepvec (T-Vec) and pembrolizumab. Conclusion: Patients who do not respond to one immunotherapy combination may respond during treatment with an alternate combination, even in the presence of multiple brain metastases. Biomarkers are needed to assist clinicians in evidence based clinical decision making after progression on first line immunotherapy to determine whether response can be achieved with second line immunotherapy.